Plakofuranolactone as a Quorum Quenching Agent from the Indonesian Sponge Plakortis cf. lita - Valeria Costantino; Gerardo Della Sala; Kumar Saurav; Roberta Teta; Rinat Bar-Shalom; Alfonso Mangoni; Laura Steindler (Marine Drugs, 2017)
There is an urgent need for novel strategies to fight drug resistance and multi-drug resistance. As an alternative to the classic antibiotic therapy, attenuation of the bacteria virulence affecting their Quorum sensing (QS) system is a promising approach. Quorum sensing (QS) is a genetic regulation system that allows bacteria to communicate with each other and coordinate group behaviors. A new γ-lactone that is capable of inhibiting the LasI/R QS system, plakofuranolactone (1), was discovered in the extract of the marine sponge Plakortis cf. lita, and its structure, including absolute configuration, was determined by NMR spectroscopy, MS spectrometry, and quantum-mechanical prediction of optical rotation. The quorum quenching activity of plakofuranolactone was evaluated using reporter gene assays for long- and short-chain signals (E. coli pSB1075, E. coli pSB401, and C. violeaceum CV026) and was confirmed by measuring the total protease activity (a virulence factor which is under control of the LasI/R system) of the wild-type P. aeruginosa PAO1. Further research will be pursued to assess the potential of plakofuranolactone as a new antivirulence lead compound and a chemical tool to increase the knowledge in this field.